2022
DOI: 10.3390/diagnostics12092069
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pathogens and Predictive Values of Biomarkers of Inflammatory Response at ICU Admission on Outcomes of Critically Ill COVID-19 Patients with Bacterial Superinfections—Observations from National COVID-19 Hospital in Croatia

Abstract: Background: Superinfections contribute to mortality and length of stay in critically ill COVID-19 patients. The aim of this study was to determine the incidence and pathogen distribution of bacterial and fungal superinfections of the lower respiratory tract (LRTI), urinary tract (UTI) and bloodstream (BSI) and to determine the predictive value of biomarkers of inflammatory response on their ICU survival rates. Methods: A retrospective observational study that included critically ill COVID-19 patients treated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…However, unlike the results in the mentioned trial, there were no significant differences in SOFA scores and P/F ratios between survivors and non-survivors. It must be noted that the increased number of antibiotic days that was recorded in non-survivors (which directly translates to rate of bacterial superinfections) was also associated with increased mortality, which was in concordance with results published from a larger cohort from our center (from which this subset of patient was extracted) by Ćurčić et al [31] In a study by Shakoor et al [32], disease severity was associated with a D-dimer cut-off of 3000 ng/mL (i.e., 3 mg/L), and patients with higher D-dimer levels were at higher risk. In our study, there were no differences in D-dimer levels between survivors and non-survivors, but patients in our study had significantly higher D-dimer levels at ICU admission (4.37, IQR 0.94-4.45 mg/L) which were probably even higher since the biochemical laboratory in our hospital does not measure values above 4.48 mg/L (if the value is greater it is displayed with an ">" operator).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, unlike the results in the mentioned trial, there were no significant differences in SOFA scores and P/F ratios between survivors and non-survivors. It must be noted that the increased number of antibiotic days that was recorded in non-survivors (which directly translates to rate of bacterial superinfections) was also associated with increased mortality, which was in concordance with results published from a larger cohort from our center (from which this subset of patient was extracted) by Ćurčić et al [31] In a study by Shakoor et al [32], disease severity was associated with a D-dimer cut-off of 3000 ng/mL (i.e., 3 mg/L), and patients with higher D-dimer levels were at higher risk. In our study, there were no differences in D-dimer levels between survivors and non-survivors, but patients in our study had significantly higher D-dimer levels at ICU admission (4.37, IQR 0.94-4.45 mg/L) which were probably even higher since the biochemical laboratory in our hospital does not measure values above 4.48 mg/L (if the value is greater it is displayed with an ">" operator).…”
Section: Discussionsupporting
confidence: 91%
“…However, unlike the results in the mentioned trial, there were no significant differences in SOFA scores and P/F ratios between survivors and non-survivors. It must be noted that the increased number of antibiotic days that was recorded in non-survivors (which directly translates to rate of bacterial superinfections) was also associated with increased mortality, which was in concordance with results published from a larger cohort from our center (from which this subset of patient was extracted) by Ćurčić et al [ 31 ]…”
Section: Discussionsupporting
confidence: 91%
“…In our study cohort, 39 (4.2%) of 930 COVID-19 patients with HABI developed IFSI in ICU, and no other comparable studies have been available. In spite of this, it is worth mentioning that a meta-analysis with most data from Central China in the early stage of pandemic found that only 8.1% of critically ill COVID-19 patients developed bacterial super-infections ( Langford et al., 2020 ), while several recent studies from different countries have reported a high incidence of HAI in ICU patients with COVID-19, with an overall rate of 65.5% (range, 50.4%-76.4%) ( Brandi et al., 2022 ; Caiazzo et al., 2022 ; Ćurčić et al., 2022 ; Hesselle et al., 2022 ; Novacescu et al., 2022 ), among which the rate of healthcare-associated IFI ranged from 5.3% to 14.6% ( Brandi et al., 2022 ; Caiazzo et al., 2022 ; Novacescu et al., 2022 ). And our model went on to reveal that COVID-19 patients were more likely to acquire IFSI during HABI.…”
Section: Discussionmentioning
confidence: 99%